2010
DOI: 10.1021/jf100714g
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin Redox Form Stabilization by Compartmentalized Lactate and Malate Dehydrogenases

Abstract: The purpose of this study was to assess the ability of mitochondrial and cytoplasmic malate dehydrogenase present in postrigor bovine skeletal muscle to use malate as a substrate for reduced nicotinamide adenine dinucleotide (NADH) regeneration and metmyoglobin (MMb) reduction via the malate-NAD(+)-MMb system. Furthermore, addition of lactate to beef mitochondrial and cytoplasmic isolates was evaluated to determine whether interactions between malate and lactate increased MMb reduction. Addition of malate to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Nevertheless, metabolism of carbohydrates can be attributed to the generation of reducing equivalents such as NADH and FADH (flavin adenine dinucleotide reduced). Mitochondrial content is greater in PM than LL (Mohan et al, 2010;Ramanathan et al, 2015) which can significantly influence the utilization of metabolites postmortem. One hundred and forty-one metabolites were identified in LL and PM.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, metabolism of carbohydrates can be attributed to the generation of reducing equivalents such as NADH and FADH (flavin adenine dinucleotide reduced). Mitochondrial content is greater in PM than LL (Mohan et al, 2010;Ramanathan et al, 2015) which can significantly influence the utilization of metabolites postmortem. One hundred and forty-one metabolites were identified in LL and PM.…”
Section: Resultsmentioning
confidence: 99%
“…Cytoplasmic malate dehydrogenase is responsible for shuttling NADH across the mitochondrial membrane via the malate-aspartate shuttle, whereas mitochondrial malate dehydrogenase is a principal enzyme of the citric acid cycle (operated within mitochondria) which catalyzes the conversion of oxaloacetate and malate utilizing the NAD/NADH coenzyme system (Minarik et al, 2002). Mohan et al (2010aMohan et al ( , 2010b reported that malate decreases metmyoglobin formation in beef muscle homogenates by generating NADH utilizing the malate dehydrogenase enzyme system, which is subsequently used for metmyoglobin reduction. The differential abundance of these enzymes indicates that different muscles could differ in their response to malate enhancement.…”
Section: Proteins Related To Energy Metabolismmentioning
confidence: 99%
“…Wittenberg & Wittenberg (2007) reported that oxygen can be delivered to cytochrome c oxidase in the inner membrane via facilitated diffusion, which results from increasing oxygen availability that occurs when oxymyoglobin is close to mitochondria. Mohan et al (2010) reported that the differences in cytochrome c oxidase activity among the three muscles (LL > psoas major > semitendinosus) corresponded well with metmyoglobin reducing activity and colour stability differences exhibited by these muscles. Ke et al (2017) reported approximately 1.8-fold difference in mitochondrial content between beef psoas major and LL muscles and suggested that greater oxygen consumption rate may possibly be detrimental to colour stability.…”
Section: Figurementioning
confidence: 77%